Reference Values for Five-Repetition Chair Stand Test Among Middle-Aged and Elderly Community-Dwelling Chinese Adults - Gao, Shan-Yan; Xia, Yang; Wu, Qi-Jun; Chang, Qing; Zhao, Yu-Hong (Frontiers in Medicine, 2021)
Background: Previous studies on the five-repetition chair stand test (CS-5) are limited by the representativeness of the sample or the lack of reference equations for CS-5. Defined reference values for CS-5 in a large population are not available for middle-aged and elderly Chinese adults. Objective: We established age- and sex-stratified reference values for CS-5 times in a large population in China, and to investigate the associations between demographic and anthropometric factors and CS-5 times. Methods: Analysis of data from the national baseline survey of the China Health and Retirement Longitudinal Study, a nationally representative longitudinal survey that includes 450 urban communities and rural villages within 28 provinces, municipalities, and autonomous regions of China. Results: 12,605 of 17,708 participants were included for the reference value analyses. 12,300 out of 17,708 participants were included for the risk factor analyses. Of 12,605 participants, the mean CS-5 time was 10.13 sec (SD, 3.32) in men and 11.03 sec (SD, 3.54) in women aged 40+ year. The CS-5 times were shorter in men than women of all age categories (P < 0.001). The cut-off points ranged from 5.36 to 9.98 sec and from 6.48 to 10.29 sec in men and women, respectively. Mean velocity was higher in men than in women (P < 0.001). Age, waist circumference, living in a rural village, and having chronic diseases were positively associated with CS-5 time, whereas male, handgrip strength, currently married, income, and current or ex-drinker were negatively associated with CS-5 time in this population (all P <0.001). Conclusions: The comprehensive normative values for CS-5 are essential for enabling clinicians to better evaluate functional performance, determine the appropriate interventional strategy, and promote healthy aging of older adults.